Profitabilitas, Likuiditas, Modal Intelektual dan Nilai Perusahaan pada Masa Pandemi Covid-19 - Astagina, Putu Diah Septa Kristya; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p13, 2023)
During the Covid-19 pandemic, the value of pharmaceutical companies increased while other companies didn't. This research aims to determine how profitability, liquidity, and intellectual capital influence firm value during the Covid-19 pandemic. The population in this research is 12 pharmaceutical sector companies listed on the Indonesia Stock Exchange (IDX) for the first quarter of 2020 to the second quarter of 2021. The sampling technique used the purposive sampling method with the number of samples obtained as many as 10 companies with 60 observations. This research used multiple linear regression analysis to determine the effect of profitability, liquidity, and intellectual capital on firm value during the Covid-19 pandemic. This research indicates that profitability, liquidity, and intellectual capital have a positive effect on firm value during the Covid-19 pandemic. Keywords: Profitability; Liquidity; Intellectual Capital; Firm Value.